Unusual effects of nanowire-nanowire junctions on the persistent photoconductivity in SnO2 nanowire network devices - Costa, I. M. [UNESP]; de Araújo, E. P.; Arantes, A. N.; Zaghete, M. A. [UNESP]; Chiquito, A. J. (IOP Publishing, 2021)
The persistent photoconductivity (PPC) effect is a commonly observed behavior in SnO2 nanostructures. Here we described and studied this effect through a comparative study, based on measurements of electronic transport using network as well as single devices built from SnO2 nanowires under different experimental conditions. At room temperature, the PPC effect was observed to be more accentuated in single nanowire devices. It was found that nanowire-nanowire junctions play a fundamental role in the device behavior: the decay time of nanowire network (τ = 52 s) is about three orders of magnitude lower than those of single nanowire (τ = 4.57 × 104 s). Additionally, it was confirmed that the PPC effect was directly related to the amount of oxygen present in the environment and it is destroyed with increasing temperature. Furthermore, the PPC effect was interpreted based on the surface effect that depends on the capture/emission of electrons by the surface states.
Keywords: Nanowires devices; Persistent photoconductivity (PPC); Tin dioxide